Choroidal Structural Changes of Posterior Subtenon Triamcinolone Acetonide Injection in Eyes with Refractory Diabetic Macular Edema - Bing Liu; Guangfeng Ma; Jing Hou; Chenyang Cong (Journal of Ophthalmology)
Purpose. To access the choroidal structural changes of posterior subtenon triamcinolone acetonide (PSTA) injection in eyes with refractory diabetic macular edema (DME). Methods. Patients with refractory DME were enrolled and followed for 4 weeks after switching to PSTA injection. All patients underwent spectral-domain optical coherence tomography with enhanced depth imaging, and the choroidal images were binarized into the luminal area and total choroidal area. Subfoveal choroidal thickness (SFCT) and choroidal vascularity index (CVI) were evaluated before and after switching treatments. Results. After switching to PSTA treatment, the final best-corrected visual acuity and central subfield thickness in eyes with refractory DME were significantly improved compared to the baseline values (P=0.002 and P<0.001, respectively). Both the SFCT and CVI decreased during the follow-up period, and significant decreases were observed at 4-week follow-up (P<0.001 and P=0.012, respectively). The linear regression analysis showed a significant correlation between the baseline SFCT and the final visual outcomes (P=0.047). Conclusions. The alterations of SFCT and CVI in this study suggest that the choroidal vasculature is involved in the pathogenesis of refractory DME and could be affected by PSTA treatment. SFCT rather than CVI may be a prognostic biomarker for eyes with refractory DME.